Robustness of densely populated urban networks in relation to the spread of traffic - Alatrista-Salas, Hugo; Núñez del Prado Cortez, Miguel; Rodríguez-López, Manuel Guillermo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
Analyzing, the morphology, robustness or vulnerability of densely populated cities is a challenge for contemporary researchers. Studies on the resilience of urban infrastructures are given by the presence of recurrent adverse events or sporadic disasters. These events force the interruption of intersections or sections of streets momentarily or permanently. For measurements we use network graph properties and computational algorithms, simulating random and targeted attacks. Finally, in the results we identify the location of critical places that contain intersections and sections of street with greater centrality of intermediation and lower average of proximity.